Analytical Study Of Hargouri Ras: An Ayurvedic Formulation - Saini, Rashmi; Porte, Sharad; Saini, Dipak (International Research Journal of Ayurveda & Yoga, 2021)
The aim of this research is to determine Hargouri Ras (A known Ayurvedic formulation used in Cancer). The objective of this study was to determine the authenticity of the medications employed in the formulation. The current study will give referential information for the proper identification and standardisation of the drug, as well as ensuring that only authentic and uniform material is used in the future manufacturing of Hargouri Ras. The test drug (Hargouri ras) was prepared in N.I.A pharmacy, under the supervision of experts and then procured for further research. The physical test like moisture content, Ph value, Alcohol Extractive, Aqueous Extractive Value, Petroleum Ether Extractive Value, Total Ash, Acid Insoluble Ash, Water Soluble Ash which is 2.43%,7.3,1.25,3.59%,0%,78.43%,67.43%,3.02% respectively for the purpose of quality control.